Analysis of the Effects of Spark Plug Type and Electrode Gap on Exhaust Emission Performance: A Case Study of the Toyota Limo - Arsy Sulaiman; Risal Abu; Mukhnizar Mukhnizar (The Future of Education Journal, 2026)
The transportation sector is the largest contributor to air pollution in urban areas due to the extensive use of fossil fuels. This study aims to analyze the effect of spark plug types and variations in electrode gap distance on the exhaust emission levels of Carbon Monoxide (CO) and Hydrocarbons (HC) in a 2008 Toyota Limo. The testing parameters utilized three types of spark plugs nickel, platinum, and iridium with variations in gap distances: standard (0.9 mm–1.1 mm), narrow (0.5 mm), and wide (1.5 mm) across various engine speeds (RPM). ​The research method involved direct testing using a Gas Analyzer at the Motor Vehicle Testing Technical Service Unit (UPT-PKB) in Padang Pariaman Regency. The collected data, comprising CO and HC emission results, were analyzed to determine the combustion efficiency within the combustion chamber. ​The results indicate that the spark plug gap distance has a more significant impact on emissions than the spark plug material itself. Using the standard gap distance consistently yielded the best emission results across all spark plug types. Overall, the iridium spark plug with a 1.1 mm standard gap produced the lowest emission levels, specifically 0.36% for CO and 55 ppm for HC at 2000 RPM. This proves that premium electrode materials produce a more focused and powerful spark, leading to more complete and environmentally friendly combustion, provided they are supported by the manufacturer's recommended gap distance